2018
DOI: 10.1073/pnas.1722042115
|View full text |Cite
|
Sign up to set email alerts
|

Coordination to lanthanide ions distorts binding site conformation in calmodulin

Abstract: The Ca-sensing protein calmodulin (CaM) is a popular model of biological ion binding since it is both experimentally tractable and essential to survival in all eukaryotic cells. CaM modulates hundreds of target proteins and is sensitive to complex patterns of Ca exposure, indicating that it functions as a sophisticated dynamic transducer rather than a simple on/off switch. Many details of this transduction function are not well understood. Fourier transform infrared (FTIR) spectroscopy, ultrafast 2D infrared (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
137
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(151 citation statements)
references
References 93 publications
5
137
2
Order By: Relevance
“…Interestingly, a recent study found that binding of Tb 3+ to another Ca 2+ -dependent protein, calmodulin, resulted in enhanced structural flexibility within Ca 2+ -binding sites and this was caused by the more electropositive Tb 3+ adopting an alternative and more disordered coordination geometry. 49 In the case of cadherins, changes in coordination geometry and flexibility within binding sites may also be the chemical driving forces behind global differences in Tb 3+ -bound and Ca 2+ -bound molecules. However, unlike in calmodulin, cadherins are non-functional upon binding to Tb 3+ , which provides further insight into the high level of sensitivity of cadherins to Ca 2+ chemistry.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study found that binding of Tb 3+ to another Ca 2+ -dependent protein, calmodulin, resulted in enhanced structural flexibility within Ca 2+ -binding sites and this was caused by the more electropositive Tb 3+ adopting an alternative and more disordered coordination geometry. 49 In the case of cadherins, changes in coordination geometry and flexibility within binding sites may also be the chemical driving forces behind global differences in Tb 3+ -bound and Ca 2+ -bound molecules. However, unlike in calmodulin, cadherins are non-functional upon binding to Tb 3+ , which provides further insight into the high level of sensitivity of cadherins to Ca 2+ chemistry.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested positive impacts of RE provision in animal husbandry, suggesting a role for REs in higher organisms. 128 However, REs are not perfect mimics of Ca, 4 as recent studies of calmodulin 129,130 and cadherin 131 have shown, suggesting that REs may not play a general role as Ca substitutes in Ca-dependent proteins. Instead, the growth-promoting effects of REs in higher organisms might plausibly be linked to the microbiome; for example, both beneficial ( E. coli ) and pathogenic ( Pseudomonas aeruginosa ) bacteria possess PQQ-dependent dehydrogenases, and these or other enzymes might benefit from or be inhibited by REs.…”
Section: Lanthanides Beyond Bacteriamentioning
confidence: 99%
“…Coherent vibrations provide structural information by changing the absorption frequencies, anharmonicity, and vibrational dynamics (26,27). Two-dimensional infrared (2DIR) spectroscopy uses a series of femtosecond mid-IR pulses to measure these properties by correlating vibrational modes, similar to how 2D NMR correlates nuclear spins (28). A pair of pump pulses excites the vibrational modes (ω pump axis), while a probe pulse measures how that mode and all of the other modes in the system respond (ω probe axis).…”
Section: Crystallin Proteins Have Large Amounts Of Native β-Sheetsmentioning
confidence: 99%